THE DEVELOPMENT OF COMPETITION IN THE ELECTRICITY MARKET (Промышленный Транспорт Казахстан, 2025)
The paper addresses the problem of development of competitive electricity markets inrelationships that were formed by the enactment of the law "On electric power industry",according to which it is prohibited to combine the activities of the transfer and sale andpurchase of electricity. The author considers types of violations of antitrust laws in the retail andwholesale electricity market, and draws conclusions on the further development of competitionin the electricity market.Since the state energy company (hereinafter RAO UES) has been established in 1992, therewere active discussions about how to develop the Russian electric power industry. Variousschemes of corporatization, privatization, consolidation with high-yielding types of industries(e.g., aluminum production), expansion of the production chain by including the production ofequipment for the power industry were proposed as the main reform ideas. Most of theseprojects were rejected due to infringement of the interests of "RAO UES" private shareholders,or contradictions to the public interest.